The why and how of corporate social responsibility in family business: a literature review. (30th July 2021) - Songini, Lucrezia; Seddio, Pasquale; Faraudello, Alessandra
This paper aims to analyse the state of the art of research on corporate social responsibility (CSR) in family business (FB), to identify the reasons why FB engages in CSR and what are main practices adopted, as well as to propose potential research gaps and future research directions. We carried out a literature review on 115 articles published since 2003. Our analysis shows that literature on CSR in FB is very recent, but sparse and fragmented. Main themes analysed concern stakeholders, disclosure, family ownership, reputation, strategy, corporate governance, socioemotional wealth, performance, environmental management, and family values. We found that a consistent and complete framework has not yet been proposed on both the determinants of CSR in FB and how they have an impact on different CSR practices. We propose that future research should thoroughly analyse different motivations that may lead different FBs to adopt a different range of CSR practices.